'Reading intercultural encounters as art': the call of the other and the relevance of beauty. (15th March 2023) - Frimberger, Katja
ABSTRACT: This article explores intercultural education research about intercultural encounters as aesthetic phenomena. I will argue that Gadamer's notion of hermeneutical identity when encountering an artwork can enrich intercultural education studies' (IES) conceptualisations of an event-based research and pedagogy, conceived as a mode of response to a personal address. Drawing on Emmanuel Levinas' ethics as first philosophy, IES's current ethical turn posits responsibility for the (radical) other (as a pre-ontological being-in-relation) – with the resulting fracturing of our self-directing ego – as the first reality of the self. In this article, I argue that Gadamer's hermeneutics speak to the curious methodological paradox, which results from IES' turn to Levinas. Here, Gadamer provokes fruitful methodological questions as to the kind of 'research aesthetic' that could plausibly emerge from such event-based research and pedagogy – when it seeks to sustain ontological/epistemological openness and not give (fully) into the 'betrayal' of (scientific) language.